High‐Performance Quantum‐Dot Light‐Emitting Diodes Using NiOx Hole‐Injection Layers with a High and Stable Work Function. (18th November 2019) - Lin, Jian; Dai, Xingliang; Liang, Xiaoyong; Chen, Desui; Zheng, Xuerong; Li, Yifei; Deng, Yunzhou; Du, Hui; Ye, Yuxun; Chen, Dong; Lin, Chen; Ma, Luying; et al.
Abstract: Solution‐processed oxide thin films are actively pursued as hole‐injection layers (HILs) in quantum‐dot light‐emitting diodes (QLEDs), aiming to improve operational stability. However, device performance is largely limited by inefficient hole injection at the interfaces of the oxide HILs and high‐ionization‐potential organic hole‐transporting layers. Solution‐processed NiO x films with a high and stable work function of ≈5.7 eV achieved by a simple and facile surface‐modification strategy are presented. QLEDs based on the surface‐modified NiO x HILs show driving voltages of 2.1 and 3.3 V to reach 1000 and 10 000 cd m −2, respectively, both of which are the lowest among all solution‐processed LEDs and vacuum‐deposited OLEDs. The device exhibits a T 95 operational lifetime of ≈2500 h at an initial brightness of 1000 cd m −2, meeting the commercialization requirements for display applications. The results highlight the potential of solution‐processed oxide HILs for achieving efficient‐driven and long‐lifetime QLEDs. Abstract : Surface‐modified NiO x hole‐injection layers with a high and stable work function offer excellent hole‐injection properties, enabling efficient‐driving and long‐lifetime quantum‐dot light‐emitting diodes.